Causes and Consequences of Inflation2. (December 2014) - Bagus, Philipp; Howden, David; Gabriel, Amadeus
Abstract While ethical implications of direct taxation systems have recently received renewed attention, a more veiled scheme remains unnoticed: inflation. We overview the causes of inflation and assess its consequences. Salient wealth redistributions are a defining feature of inflation, as savers and fixed income individuals see a relative wealth reduction. While avoiding this "tax" is difficult in many instances because of the primacy of money in a monetary economy, the tax codes of most developed countries allow avoidance techniques to be employed. We analyze three ways that inflation may be avoided in an attempt to preserve personal wealth, as well as the consequences of such practices.